Air Pollution and Health: The Need for a Medical Reading of Environmental Monitoring Data - Iriti, Marcello; Piscitelli, Prisco; Missoni, Eduardo; Miani, Alessandro (International journal of environmental research and public health, 2020)
Air pollution is a recent public health issue. In 2006, the World Health Organization (WHO) published updated air quality guidelines for a number of air pollutants (including PM10 and PM2.5), which recommended for particulate matter annual average concentration levels at half or less the limit values set by European legislation. In the European Union, around 80% of the European urban population is exposed to air pollution above the levels recommended by the WHO guidelines. Only in 2015 the WHO addressed for the first time the topic of the health impacts of air pollution in its general assembly, which adopted a resolution clearly defining air pollution as the world’s largest single environmental health risk factor. Nowadays, the WHO considers air pollution as a major public health threat, causing a 7% increase in overall mortality for each increase of 10 μg/m3 in annual average of PM2.5. This result has been achieved thanks to the outstanding efforts of the director of the WHO’s Environment and Public Health Department, Dr. Maria Neira, who has devoted her full commitment to highlighting the consequences that air pollution has on people’s health. More recently, at European level, the Air Quality Directive has been subject to a fitness check, published in 2019; the European Green Deal has since announced its aim to align EU air quality standards more closely with the WHO recommendations. Every year, the European Environment Agency (EEA) publishes its “Air Quality in Europe” Report to assess the figures on air pollution across Europe and related health impacts. However, environmental data provided by official regional or national agencies—used by decision makers to adopt preventive measures such as limitations on urban traffic or domestic heating—refer to legal thresholds established by the law (usually on the basis of values set at European level, at least for the EU). These legal thresholds, however, are not adequate to fully protect population against all impacts from air pollution as recommended by WHO and scientific evidence. Therefore, we point out the need for a medical reading of environmental monitoring data that should be performed both at national and regional or local level by health authorities, to foster population health protection against air pollution and guarantee the application of the precautionary principle. A stronger cooperation between environmental agencies and health authorities is needed to address the new challenges to human and planetary health arising from air pollution and climate change. Health authorities should integrate their medical staff with new professionals and researchers with adequate training in environmental sciences to foster population health protection against air pollution. For this purposes, multi-disciplinary research units or teams should be established by local health authorities on environmental health topics, working together with medical staff and environmental agencies for a mutual integration of competencies.